Analyzing the Causes and Factors Affecting the Gender Wage Gap (In Light of the Principle of Equal Pay in International Labor Law) - Fatemeh Nowrouzi (پژوهشهای حقوقی)
The gender wage gap has violated the principle of equality and non-discrimination and the principle of equal pay. In this regard, the International Labor Organization, while recognizing and emphasizing the principle of equal pay for work of equal value in its conventions and recommendations, has conducted research and prepared a report in this field as well. This guide can provide appropriate and necessary policy recommendations to governments. It should be emphasized that the gender wage gap represents a very broad problem, both in societies and in the labor market, that cannot be solved individually. Research has shown that gender pay equity should be pursued through a policy program that promotes an inclusive and transparent labor market alongside the application of the principle of pay equity. Women's economic empowerment has obvious positive consequences for women's agency, freedom, and social and political empowerment. Unequal wages during working years have their effects on gender inequality throughout life, and lower income reduces women's economic independence throughout life, and Its consequences are evident in old age in salaries and income during retirement. The present study, with a descriptive-analytical method, aims to analyze the causes and factors affecting the gender wage gap; Because eliminating the gender pay gap depends on knowing how and to what extent such gaps exist. The results indicate that the factors affecting the gender wage gap are rooted in the human capital model and the discrimination model, which each explain a part of the gap.